The Strategic Management of Administrators and School Efectiveness Under Nakorn Pathom Primary Educational Service Area Office 1 - Kampom, Parichat; Inrak, Prasert (Journal of Dhamma for Life, 2024)
The purposes of this research were identify :1.) To know the strategic management of educational institutions under the Nakorn Pathom Primary Education Area Office. District 1 2.) To know the effectiveness of educational institutions under the Nakorn Pathom Primary Education Area Office District 1 3.) To know the strategic management relationships that affect the effectiveness of educational institutions under the Nakorn Pathom Primary Education Area Office District 1 The sample In the research was 92 schools under the Nakorn Pathom Primary Education Area Office District 1. 1 person 1 teacher, total 184 students The instrument used in the research was a questionnaire on strategic management based on Thomas L. Wheelen and J. David Hunger and others, and the effectiveness of educational institutions according to Mott’s concept. The statistics used in the data analysis are frequency, percentage, standard deviation and Pearson correlation coefficient. The research findings were as follows: Strategic management Overall, it was found that strategic management of the school was under the Nakorn Pathom Primary Education Area Office. District 1 is at most 1 side and 4 extreme in descending order of arithmetic values. The effectiveness of educational institutions under the office of Nakorn Pathom Primary Education Area District 1 as a whole and individually is as a high level. In descending order of arithmetic values: Transformation and Development Ability; 2.) Ability to produce students with positive attitudes 3.) Ability to produce students with high academic achievement 4.) Ability solve problems within the school.Strategic management and school effectiveness Affiliatio n with Nakorn Pathom Primary Education Area Office District 1 was statistically significant at the level of .01, which is correlated in an amenable manner.